SUBMERSIBLE PUMP EVALUATION OF SELECTION SYSTEM OF PDAM TIRTAULI IN SIANTAR SELATAN DISTRICT, PEMATANGSIANTAR CITY IN 2018 - Hanindya, Beta; O. Brusa, Jorge; Kurniawan, Hendri; Mustaruddin, Mustaruddin; Sanjaya, Muharti (International Conference on Health Science, Green Economics, Educational Review and Technology, 2020)
In this Final Project a submersible pump type pump has been applied. From the data pump the capacity is 27.10 l / sec. The pump head is 14.62 m based on calculations in the field. By using empirical equations, we can determine the main parameters of pump planning, namely specific speed, pressure loss on the pipe wall, length, diameter and type of pipe, the number and type of pipe accessories used.By conducting research and measurements on the field obtained a 6 inch pipe diameter, Ci type and 1260 meter pipe length using Hazen William formula and continuity of flow and pressure loss along the pipe (loss head friction) and pressure loss (minor loss head) is 20.50 meters.